Clinicopathological Study of Oral Cancer* - F. M. Tripathi; S. Khanna; N. N. Khanna; C. T. S. Chari; J. K. Sinha (Indian Journal of Plastic Surgery, 1977)
Present study is based on the observations of 25 cases of oral cancer. Males are affected more commonly in S5th and 6ih decade. Clinical lymphadenopathy in the neck is observed in 84% of cases which was confirmed on hisiology in only 56% cases. Clinically the disease is more advanced than its histological grade. Inflammatory infiltrate in the primary tumour and germinal centre hyperplasia, paracortical activity and sinus histiocytosis in the Iymphnodes are suggestive of immunological response against the tumour whereas capsular and pericapsular invasion of lymph nodes are suggestive of poor prognosis.